Optimizing Madrasah Teacher Performance: The Role of Training and Total Quality Management - Syaifullah; Ria Mardiana Yusuf; Ami Pujiwati; Zainur Hidayah (Universitas Medan Area, 2025)
The quality of education in Madrasah schools depends significantly on how teachers perform. This study evaluates how Total Quality Management (TQM) and teacher training programs affect teacher performance while examining TQM as a moderating factor. The research employs a quantitative design which adopted simple random sampling through the Slovin formula to select 303 respondents from a population of 1,245 teachers spread across 13 cities and regencies. The researchers gathered data through questionnaires and applied Structural Equation Modeling (SEM) using PLS software to analyze these da-ta. The results demonstrate significant positive effects of training programs and TQM on teacher performance while showing that TQM strengthens the impact of training on teacher performance. TQM increases the effect of training on teacher performance by promoting data-driven decision-making, and a culture of continuous improvement. The findings demonstrate that educational quality will advance through the integration of TQM into teacher training programs. The recommendation aligns with the findings that support establishing a systematic teacher training framework based on TQM in Madrasah education to improve learning results.